ANALISA DAN DESAIN SISTEM INFORMASI PEMBAYARAN SPP DAN BIAYA SEKOLAH: (STUDI KASUS PADA YAYASAN MANDALAHAYU BEKASI) - Uus Rusmawan; Imam Mulya (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2023)
Currently private schools are starting to emerge in various places with various levels of education ranging from PAUD, Kindergarten, Elementary School, Middle School, MTs, High School, Vocational School and even tertiary institutions. An educational institution definitely needs a data processing system for tuition payments and other costs such as building fees, LKS, Eskul, Student Council and the like for the continuity of the institution's operations. The problems that most often arise in this case are reports of payments that have been paid and arrears grouped based on certain criteria. The report is very important as a basis for decision making for school management to improve service and quality of education. The Mandalalahayu foundation is an institution engaged in the field of education starting from the early childhood or kindergarten, elementary, MI, junior high, MTs, high school and vocational school levels. The management of school administration fee payments is quite complicated because there are several levels of education. It is on this basis that this research needs to be carried out. The method used is Rapid Application Development (RAD), an application made with desktop programming using VB.Net and Sqlserver. Application testing using blackbox. The results of this study can be used for all levels of education from kindergarten to tertiary institutions and even for all types of school or campus fee payments in general.